Strategi Guru dalam Meningkatkan Kemampuan Bahasa Anak Usia 5-6 Tahun Melalui Media Balok Huruf - Astini, Baik Nilawati; Alkaida, Randa; Hasanah, Uswatun; Ice, Ice (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Hanging letter block media is a combination of games and learning aimed at improving children's letter recognition, vocabulary, and language skills. Early childhood is in a stage of rapid development, so effective learning can affect their language skills. The purpose of this study is to analyze teachers' strategies in improving the language skills of children aged 5-6 years through the medium of hanging letter blocks. This study uses a literature study method, by analyzing various articles and books related to the use of this media in early childhood learning. The source of data for this research is scientific articles from Google Scholar. The data analysis technique used is the content analysis technique. The results of the study showed that the use of hanging letter block media was effective in improving children's language skills, as well as supporting fine motor development and cognitive skills. Despite challenges such as the need for more intensive mentoring and the duration of activities that need to be adjusted, this media can improve children's language skills and social-emotional skills. The development of this media with a variety of images and letters can increase its effectiveness in learning.